2009
DOI: 10.1029/2009gb003500
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical iron budgets of the Southern Ocean south of Australia: Decoupling of iron and nutrient cycles in the subantarctic zone by the summertime supply

Abstract: [1] Climate change is projected to significantly alter the delivery (stratification, boundary currents, aridification of landmasses, glacial melt) of iron to the Southern Ocean. We report the most comprehensive suite of biogeochemical iron budgets to date for three contrasting sites in subantarctic and polar frontal waters south of Australia. Distinct regional environments were responsible for differences in the mode and strength of iron supply mechanisms, with higher iron stocks and fluxes observed in surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
245
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(277 citation statements)
references
References 92 publications
28
245
4
Order By: Relevance
“…The elevated biomass observed at P3, which is present throughout the year as indicated by satellite remote sensing (Mongin et al, 2011), was not accompanied by elevated primary or new production, and did not translate into increased sinking flux, at least not during the short shipboard observational period reported here. This provides a cautionary note, as have other studies of natural iron fertilisation (Blain et al, 2007;Pollard et al, 2007), about the effectiveness of iron inputs (which were elevated at the P3 site; Bowie et al, 2009) to increase biological pump strength. The clear influence of zooplankton grazing in the control of particle production and export observed via the use of the polyacrylamide gel traps emphasises the influence of higher trophic levels on biological pump responses to stimulation of photosynthesis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The elevated biomass observed at P3, which is present throughout the year as indicated by satellite remote sensing (Mongin et al, 2011), was not accompanied by elevated primary or new production, and did not translate into increased sinking flux, at least not during the short shipboard observational period reported here. This provides a cautionary note, as have other studies of natural iron fertilisation (Blain et al, 2007;Pollard et al, 2007), about the effectiveness of iron inputs (which were elevated at the P3 site; Bowie et al, 2009) to increase biological pump strength. The clear influence of zooplankton grazing in the control of particle production and export observed via the use of the polyacrylamide gel traps emphasises the influence of higher trophic levels on biological pump responses to stimulation of photosynthesis.…”
Section: Discussionmentioning
confidence: 89%
“…Increased iron supply is observed in this region of the SAZ (Bowie et al, 2009), as are surface biomass levels as observed by satellite remote sensing (Mongin et al, 2011). Thus, this site offers the opportunity to observe the response of export to natural iron inputs to the Subantarctic Zone, which can be compared to other Southern Ocean natural iron fertilisation studies such as CROZEX (Pollard et al, 2007) and KEOPS (Blain et al, 2007).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Using similar assumptions as above, we estimate that the long-term iron removal through incorporation into silica is B23 mmol m À 2 per year. Although a higher level of biologically relevant iron sequestration may occur over shorter timescales through the export of silica below the mixed layer, the major inputs of bioavailable iron to the Southern Ocean through lateral advection (for example, 9-45 mmol m À 2 per year) 25 and atmospheric deposition (for example, 1-30 mmol m À 2 per year) [25][26][27] are comparable to this long-term sink. As in the Ross Sea, the removal of iron through silica burial in the Southern Ocean may be a profound factor controlling the bioavailable pool of iron and, therefore, the primary productivity.…”
Section: Discussionmentioning
confidence: 96%
“…As in the Ross Sea, the removal of iron through silica burial in the Southern Ocean may be a profound factor controlling the bioavailable pool of iron and, therefore, the primary productivity. Indeed, our estimated long-term iron removal flux through silica burial can account for B30-90% of the export of particulate iron from surface waters in several typical systems of the Southern Ocean 25 . Similarly, removal of iron through incorporation into silica may also have a substantial role in the high-nutrient, lowchlorophyll equatorial Pacific, where iron burial is integrally, yet enigmatically, coupled to silica deposition 28 .…”
Section: Discussionmentioning
confidence: 99%